1993
DOI: 10.1007/bf00195761
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical implications of collagen fibre orientation in cortical bone of the equine radius

Abstract: Abstract. Mechanical test specimens were prepared from the cranial and caudal cortices of radii from eight horses. These were subjected to destructive tests in either tension or compression. The ultimate stress, elastic modulus and energy absorbed to failure were calculated in either mode of loading. Analysis was performed on the specimens following mechanical testing to determine their density, mineral content, mineral density distribution and histological type. A novel technique was applied to sections from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
163
2

Year Published

1996
1996
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(173 citation statements)
references
References 41 publications
8
163
2
Order By: Relevance
“…However, it is too early to draw the conclusion from these results. Riggs et al (1993b) analyzed the collagen fiber orientation of the equine radius and revealed the contrasting relation between four quadrants. Potentially, this implies that the variation of material properties or microstructure may differ between species or bone types.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is too early to draw the conclusion from these results. Riggs et al (1993b) analyzed the collagen fiber orientation of the equine radius and revealed the contrasting relation between four quadrants. Potentially, this implies that the variation of material properties or microstructure may differ between species or bone types.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of the horse radius (Boyde and Riggs, 1990;Mason et al, 1995;Riggs et al, 1993a,b); the macaque circumorbital region (Bromage, 1992); and the calcanei of horse, sheep, and elk (Skedros et al, 1997) helped to support existing hypotheses of the relationship between preferred collagen fiber orientation and mechanical loading. Martin and Ishida (1989), Martin and Boardman (1993), and Riggs et al (1993b) examined several material properties of bone and determined that collagen fiber orientation made the most significant contribution to the overall strength of bone tissue. McMahon et al (1995) presented data from the sheep calcaneus, suggesting this relationship might be more complex than previously thought: the authors propose that low levels of localized tension may have a more significant impact on collagen fiber distribution than higher levels of peak compression in regions of some bone elements.…”
Section: Polarizing Light Microscopy Of Bonementioning
confidence: 99%
“…Among them, the significant contribution of the orientation and arrangement of bone's ultrastructure to its mechanical properties has long been suggested [30 -33] and experimentally investigated [34][35][36][37][38][39][40][41]. In addition, several studies conducted at different structural scales have shown that ultrastructure orientation and arrangement are among the best predictors of mechanical properties such as bone strength or elastic modulus [42][43][44][45]. Many approaches have been proposed in previous years to investigate the threedimensional (3D) orientation of at least one of the four structural elements of bone ultrastructure mentioned above, including methods based on visible light, X-rays, electrons or magnetic fields, with some of them providing very promising results.…”
Section: Introductionmentioning
confidence: 99%